Matematika/Evoliutė ir evolventė: Skirtumas tarp puslapio versijų

Jump to navigation Jump to search
:<math> x_M =\frac{y_M\sin t+a}{\cos t},</math>
:turi tenkinti sąlygą:
:<math>\sqrt{(x_M-\alpha-x_m)^2+(\beta -y_M)^2}=at,</math>
:arba
:<math>(\alpha-x_m)^2+(\beta -y_M)^2=a^2 t^2,</math>
:<math>(ax_M- \cos(t) -x_malpha)^2+(a\sin(t)beta -y_M)^2=a^2 t^2,</math>
:<math>(\alphax_M-x_ma\cos(t))^2+(a\betasin(t) -y_M)^2=a^2 t^2,</math>
:<math>(x_M^2-2a x_M\cos(t)+a^2\cos^2 t)+(a^2\sin^2(t) -2a y_M\sin(t)+y_M^2)=a^2 t^2,</math>
5 067

pakeitimai

Naršymo meniu